Street art as everyday counterterrorism? The Norwegian art community's reaction to the 22 July 2011 attacks. (June 2019) - Tellidis, Ioannis; Glomm, Anna
This article looks at a project involving nine internationally acclaimed street artists who agreed to make murals in Oslo, following the 22 July 2011 attacks. Resting on the art project's aims ('to promote universal human rights and to counter the intolerance and xenophobia that can give rise to violence and justify terrorism') and the art community's reaction, the article argues that street art's visibility and agency offer alternative ways of thinking about, and approaching, international relations (IR). The article examines the streets as the space where artists express and engage the 'everyday'; and as the medium that allows artists to bring art to the public (as opposed to galleries or exhibitions the public chooses to visit). We argue that the incorporation of street art's spatiality and aesthetics into 'everyday IR' supports more critical frameworks that (a) expose the exceptional logic(s) of illiberal governance; (b) enable the visibility of marginalised and/or dissenting voices in society; and (c) explore experimental, eclectic and creative approaches of doing/thinking everyday security, community and peace.